Purification of Monoclonal Antibodies Using Chromatographic Methods: Increasing Purity and Recovery - Elnazalsadat Jafarzadeh Chehraghi; Parvin Akbarzadehlaleh; Karim Shamsasenjan (Advanced Pharmaceutical Bulletin)
Monoclonal antibodies (mAbs) have gained increasing significance in biopharmaceutical research and production because of their precise targeting and therapeutic potential. The purification of mAbs is a crucial stage in production, ensuring the elimination of impurities for a top-quality, safe, and efficient final product. Chromatographic methods including affinity chromatography, ion exchange chromatography, and hydrophobic interaction chromatography (HIC) are commonly utilized to selectively capture and purify mAbs from complex mixtures by exploiting their unique properties, such as antigen-binding specificity or their surface charge and hydrophobicity. This review provides an overview of the current chromatographic techniques for mAbs purification, and to this aim delves into recent advancements and emerging trends in mAb purification, including the application of multi-modal ligands, membrane adsorbers, and continuous processing. These innovations aim to enhance efficiency, selectivity, and reliability while reducing processing time and costs, ultimately contributing to the development of safe and effective mAb-based therapies. Emphasis is placed on the necessity of choosing suitable methods based on the unique properties of the mAb and the desired quality attributes of the end product.